2017
DOI: 10.3390/ma10030246
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Epoxy Resin Mortar with Sand Washing Waste as Filler

Abstract: The objective of this study was to investigate the potential use of sand washing waste as filler for epoxy resin mortar. The mechanical properties of four series of mortars containing epoxy binder at 10, 15, 20, and 25 wt. % mixed with sand blended with sand washing waste filler in the range of 0–20 wt. % were examined. The compressive and flexural strength increased with the increase in epoxy and filler content; however, above epoxy 20 wt. %, slight change was seen in strength due to increase in epoxy and fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…After the drying process, the bond strength to the surface is greater than 2 MPa (tab. 4), which is comparable with commonly used epoxy resins [14]. Weight loss.…”
Section: Resultsmentioning
confidence: 56%
“…After the drying process, the bond strength to the surface is greater than 2 MPa (tab. 4), which is comparable with commonly used epoxy resins [14]. Weight loss.…”
Section: Resultsmentioning
confidence: 56%
“…Currently, there is a tendency to the use of man-made waste as fillers for polymer solutions based on epoxy resins [9,10]. The use of such fillers provides reduce in the cost of material, and the use of iterative numerical methods makes possible to obtain the compromise-optimal compositions with guaranteed properties.…”
Section: Discussion Of Results Of Studying the Properties Of Epoxy Comentioning
confidence: 99%
“…In addition, the use of fillers is one of the ways to control properties of epoxy solutions directly. There are studies on strength characteristics of epoxy composites with various types of filler [9,10]. Authors of work [9] found that the replacement of silica sand with porous fillers and rubber crumb leads to deterioration in strength characteristics of epoxy compositions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…To determine the exact cause of this difference, additional research is required. According to previous studies on the moduli of elasticity of EP polymer concrete mixtures, Lokuge et al [5] reported levels ranging from 9.5 to 11 GPa, Hassan et al [20] showed 13.2 GPa, According to previous studies on the moduli of elasticity of EP polymer concrete mixtures, Lokuge et al [5] reported levels ranging from 9.5 to 11 GPa, Hassan et al [20] showed 13.2 GPa, According to previous studies on the moduli of elasticity of EP polymer concrete mixtures, Lokuge et al [5] reported levels ranging from 9.5 to 11 GPa, Hassan et al [20] showed 13.2 GPa, Decter et al [31] demonstrated 0.5 to 20 GPa, and Yemam et al [32] found 8 to 18 GPa. These moduli of elasticity were affected by the type of EP, its contents, the properties of the aggregate, test method employed, temperature, and specimen size.…”
Section: Modulus Of Elasticitymentioning
confidence: 96%
“…This is an excellent property when the material is used in precast applications. [31] identified between 50 and 100 MPa, and Yemam et al [32] indicated 36 to 103 MPa. In particular, Golestaneh et al [34] showed the highest compressive strength of 128.9 MPa when using silica flour as a filler, which is similar to the test results of this study.…”
Section: Modulus Of Elasticitymentioning
confidence: 97%